Gambaran Pelaksanaan Perawatan Luka dan Kejadian Infeksi Luka Operasi post Sectio Caesarea - Astriani, Luh Putu Ninik; Widyawati, Widyawati; Aulawi, Khudazi (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2007)
Please refer to the file